Articulação de políticas públicas para inclusão da pessoa com deficiência no trabalho: uma análise da atuação do ministério público do trabalho junto às empresas privadas em Goiânia - Manjela, Dyeire Nayara Garcia (2024)
This study aims to discuss the effectiveness of public policy articulation for the inclusion of Persons with Disabilities (PwD) in private companies in Goiânia. It presents a historical and conceptual analysis of the right to inclusion, with an emphasis on the inclusion of PwD in the workplace; it exposes the norms for labor protection and inclusion of PwD with the aim of rethinking quotas in the private sector and identifying challenges and possibilities for effective inclusion in private companies; it discusses the role of the Public Ministry of Labor (PML) in Goiânia regarding the main strategies employed for the inclusion of PwD; it addresses the articulation of public policies and institutional design with a view to the implementation of Supported Employment; and presents a proposal for a draft bill aimed at expanding the quota system by hierarchical level, highlighting the importance of representativeness at all hierarchical levels, given the current challenges of the existing quota system. The methodology used in this research was bibliographic and documentary research combined with a case study. The empirical research focused on the analysis of Processes and Procedures at the 18th Regional Prosecutor's Office of the Public Ministry of Labor (2012- 2022) to verify whether, regarding the compliance with quotas, the public policies overseen by the Public Ministry of Labor (PML) have indeed proven effective. It was found that there is a gap between legislative intent and practical effectiveness, such that judicial intervention is often necessary to ensure compliance with quotas. Another finding made clear the preference of companies to hire PwD who presumably require fewer adaptations, evidenced by the fact that most of the hires were of physical PwD, while other types of disabilities had much lower percentages. However, concerning the responses to the identified problems, it is understood that collaborative measures in the implementation phase, such as supported employment, present as promising solutions. The widespread adoption of these practices by all involved agents may lead to significant advancements in the inclusion of PwD in the labor market. In this sense, the draft bill suggested in this work, which proposes the expansion of the quota system by hierarchical level, can greatly contribute. Also, it is important to highlight that institutions belonging to the "S" services have sought to fulfill their role in meeting the demands of companies, offering activities aimed at the professional qualification of people with disabilities and investing in the updating and training of teachers and professionals, thus being committed to expanding and improving actions related to the professional preparation of young and adult people with disabilities and/or rehabilitated by the INSS, increasing their competitiveness and employability, considering the profile of the business sector's demand.